EKSISTENSI SUBAK DI BALI: MAMPUKAH BERTAHAN MENGHADAPAI BERBAGAI TANTANGAN - NYOMAN SUTAWAN (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2001)
This paper discusses the present and future challenges faced by the Balinese subak.Those challenges are: increasing competition in the marketing of agricultural products due tothe trade liberalization; the declining interest of the rural youth to work as farmers; financialburden of the farmers due to irrigation management transfer and payment of irrigation servicefee; the decline of irrigated land areas due to the conversion for other uses; degradation ofenvironment; and limited availability of water resources.It is argued that subak has strengths and therefore may be able to cope with suchchallenges because subak is indeed a viable institution as indicated by the fact that it has beenin existence for many centuries. However, subak also has some weaknesses. It is necessarytherefore, that some efforts need to be done to empower subak so that it can survive to copewith those challenges.